2022
DOI: 10.1155/2022/2154599
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the Effect of Integrated Care on Preoperative Anxiety in Day Surgery Patients Based on the MVPA Framework

Abstract: Objective. To investigate the effect of receiving comprehensive care on preoperative anxiety in patients admitted to the operating room at different times. Methods. A generative model was applied to a patient’s preoperative anxiety aid diagnostic model and used to address preoperative anxiety due to the patient. Group ICA first constructed a whole-brain dynamic functional connectivity network, and an initial dataset was constructed by Kendall’s ranking correlation coefficient method; then, an expanded dataset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%